طرق الإمام أحمد في الاستنباط من القرآن - Hasanulddin, Mohd; Omar Ahmed, Ahmed Moqbel Mareai (2018)
Al-Quran has been revealed by Allah SWT consisting all of the religion teachings, a few of them explained in detail and lots of it still in general (mujmal). Thus, Allah delegates the explanation of His Quran to the Muhammad PBUH so that the Sunnah will discuss the laws brought by Quran in detail. The secrets of such explanations only could be understood by the scholars who have the greatest knowledge and the deepest pious. That is happening to Imam Ahmed ibn Hanbal, a great scholar among the greatest in term of al-Qur’an, Sunnah and Islamic jurisprudence teachings. Therefore, the factor brings the study to be carried out, to fulfill the needs of community and its problems through the methods based on ijtihadic approach. This approach is only can be conducted by the specialist who fulfill all of its conditions. The study collects data form al-Qur’an, Sunnah and other resources such as Islamic authoritative jurisprudence books. Its aims are to describe the concept of istinbat (the production process of Islamic laws), its types and the Sharia goals from its existence at any authoritative source. Then, this kind of istinbat will be implemented on the several jurisprudence issues whether the source is firm or not in term of its clues. The differences of Islamic jurisprudence approachment also will be expressed in this matter. As conclusion, we should know the concept of istinbat is very important to be take care of. We need more study and research to explore especially the principles and ways of istinbat and the implementations of istinbat from the scholars books, such as Imam Ahmad to bring out the Islamic laws and its goals from al-Qur’an.